2021
DOI: 10.1038/s41598-021-82789-x
|View full text |Cite
|
Sign up to set email alerts
|

Combined analysis of gestational diabetes and maternal weight status from pre-pregnancy through post-delivery in future development of type 2 diabetes

Abstract: We examined the associations of gestational diabetes mellitus (GDM) and women’s weight status from pre-pregnancy through post-delivery with the risk of developing dysglycaemia [impaired fasting glucose, impaired glucose tolerance, and type 2 diabetes (T2D)] 4–6 years post-delivery. Using Poisson regression with confounder adjustments, we assessed associations of standard categorisations of prospectively ascertained pre-pregnancy overweight and obesity (OWOB), gestational weight gain (GWG) and substantial post-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
36
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 44 publications
(19 reference statements)
0
36
0
Order By: Relevance
“…There is also accumulating evidence that maternal obesity-driven GDM leads to long-term (programmed) effects in the offspring [ 5 , 6 , 7 , 8 , 9 , 10 , 11 ], suggesting that GDM and its risk factors have inter-generational effects. There is an increased risk of both cardio-vascular disease and type 2 diabetes mellitus (T2DM) in the decade after delivery in individuals who developed GDM [ 12 , 13 , 14 , 15 , 16 ]. Research in this area includes a systematic review of over 5 million women across nine studies that found that women who developed GDM had a two-fold increased risk of cardiovascular events independent of developing T2DM [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is also accumulating evidence that maternal obesity-driven GDM leads to long-term (programmed) effects in the offspring [ 5 , 6 , 7 , 8 , 9 , 10 , 11 ], suggesting that GDM and its risk factors have inter-generational effects. There is an increased risk of both cardio-vascular disease and type 2 diabetes mellitus (T2DM) in the decade after delivery in individuals who developed GDM [ 12 , 13 , 14 , 15 , 16 ]. Research in this area includes a systematic review of over 5 million women across nine studies that found that women who developed GDM had a two-fold increased risk of cardiovascular events independent of developing T2DM [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…There is an increased risk of both cardio-vascular disease and type 2 diabetes mellitus (T2DM) in the decade after delivery in individuals who developed GDM [12][13][14][15][16]. Research in this area includes a systematic review of over 5 million women across nine studies that Int.…”
Section: Introductionmentioning
confidence: 99%
“…It should be noted that both diabetes combined with pregnancy and GDM would cause blood glucose to increase in pregnancy 16 . The medical record provided by outpatient departments had discriminated against these two conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the proper management of hyperglycemia during pregnancy is an important opportunity to reduce the risk of these conditions. 3 , 4 …”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the proper management of hyperglycemia during pregnancy is an important opportunity to reduce the risk of these conditions. 3,4 Most patients with GDM can control their blood glucose within the normal range through standardized management, diet adjustment, reasonable exercise, and timely monitoring. Therefore, on the basis of individualized dietary interventions and exercise guidance, patients were advised to participate in the one-day clinic DM management model in our hospital.…”
Section: Introductionmentioning
confidence: 99%